Analisis Customer Value pada Perancangan Aplikasi E-Procurement di PT Indesso Aroma - Henkie Ongowarsito (Bina Nusantara University, 2011)
More online business applications are utilized by companies; one of which is e-procurement. PT Indesso Aroma as a manufacturing company of essential oils, natural extracts, and aromatic chemicals products needs to improve its conventional procurement process to e-procurement to be more effective and efficient. For that, a research is conducted towards the performance and interest of the company's procurement system. Furthermore, the current SAP system application support is developed, as the customer values are analyzed using gap analysis to see the benefits of its application for the company. The e-procurement design uses OOAD method with UML diagram notation including analysis of problem domain, application domain, architectural design and component design. Cost-benefit analysis is performed to see an increase in customer value from the e-procurement application based on measurements of NPV, IRR and ROI of investing in the e-procurement design. Thus an e-procurement application is created that is expected to improve the company’s procurement process with several key features such as Purchase requisition, Purchase Order, Purchase Return, Supplier Catalog and Supplier Quotation.